Cinco Joias de Coimbra: Património Mundial da Humanidade - Gouveia Monteiro, João; Leonor Cruz Pontes, Maria (Coimbra University Press, 2025)
This work revisits five key pieces of the classification of «Coimbra – Alta – Sofia» as a World Heritage Site: the King John’s Library, the São Miguel Chapel, the Baroque organ of the chapel, the Botanical Garden and the Machado de Castro National Museum. The trip is guided by top experts who, in their chapters, not only summarize essential historical information about each of the revisited places, but also add, in several cases, important news.